Aggregation-based detection of M. smegmatis using d-arabinose-functionalized fluorescent silica nanoparticles. Issue 88 (17th September 2015) - Jayawardana, Kalana W.; Wijesundera, Samurdhi A.; Yan, Mingdi
Abstract : d -Arabinose-conjugated nanoparticles interacted strongly with Mycobacterium smegmatis and caused the bacteria to aggregate. Mycobacteria at concentrations as low as 10 4 CFU per mL were detected by this aggregation method. Abstract : Fluorescein-doped silica nanoparticles (FSNPs) functionalized withd -arabinose (Ara) showed strong interactions with Mycobacterium smegmatis ( M. smegmatis ) and caused the bacteria to aggregate. This aggregate formation was used as a means to detect M. smegmatis at the concentration of 10 4 CFU per mL.